The primary care of a patient with a history of a gastrointestinal malformation and abdominal wall or diaphragmatic defects - Jordi Prat-Ortells; Xavier Tarrado (Elsevier, 2019)
Survival of patients with congenital malformation has improved over the last decades. Primary Care paediatricians must be aware of the most common problems that this group of patients suffers. More importantly, paediatricians can offer a holistic view that is often lost in specialised consultation.This article is focused on common congenital malformation, such as oesophageal atresia, abdominal wall defects, anorectal malformation, Hirschsprung disease, and congenital diaphragmatic hernia. The main problems are shown, with special emphasis on long-term complications and all the dimensions of the individual. Resumen: La supervivencia de los pacientes con antecedentes de malformaciones congénitas complejas ha aumentado en las últimas décadas. El pediatra de atención primaria debe conocer los problemas más habituales que pueden sufrir este grupo de pacientes. Además, puede ofrecer una visión global que, a menudo, se pierde en las consultas especializadas.En este trabajo se recogen algunas de las malformaciones congénitas digestivas y respiratorias más habituales como la atresia de esófago, defectos de pared abdominal, malformación anorrectal y enfermedad de Hirschsprung y la hernia diafragmática congénita. Se señalan los problemas de mayor interés para el pediatra, haciendo hincapié en las complicaciones a largo plazo y en todas las dimensiones de la persona.